The First Optimization Process from Cultivation to Flavonoid-Rich Extract from Moringa oleifera Lam. Leaves in Brazil - Larissa Marina Pereira Silva; Maria Raquel Cavalcanti Inácio; Gualter Guenter Costa da Silva; Jucier Magson de Souza e Silva; Jefferson Romáryo Duarte da Luz; Maria das Graças Almeida; Edgar Perin Moraes; Debora Esposito; Leandro De Santis Ferreira; Silvana Maria Zucolotto (Foods, 2022)
Flavonoids are significant antioxidant and anti-inflammatory agents and have multiple potential health applications. Moringa oleifera is globally recognized for its nutritional and pharmacological properties, correlated to the high flavonoid content in its leaves. However, the bioactive compounds found in plants may vary according to the cultivation, origin, season, and extraction process used, making it difficult to extract reliable raw material. Hence, this study aimed to standardize the best cultivation and harvest season in Brazil and the best extraction process conditions to obtain a flavonoid-rich extract from M. oleifera as a final product. Firstly, ultrasound-assisted extraction (UAE) was optimized to reach the highest flavonoid content by three-level factorial planning and response surface methodology (RSM). The optimal cultivation condition was mineral soil fertilizer in the drought season, and the optimized extraction was with 80% ethanol and 13.4 min of extraction time. The flavonoid-rich extract was safe and significantly decreased reactive oxygen species (ROS) and nitric oxide (NO) in LPS-treated RAW 264.7 cells. Lastly, the major flavonoids characterized by HPLC-ESI-QTRAP-MS/MS were compounds derived from apigenin, quercetin, and kaempferol glycosides. The results confirmed that it was possible to standardize the flavonoid-rich extract leading to a standardized and reliable raw material extracted from M. oleifera leaves.